Integrating Network Pharmacology with in vitro Experiments to Validate the Efficacy of Celastrol Against Hepatocellular Carcinoma Through Ferroptosis - Cai B; Qi M; Zhang X; Zhang D (Dove Medical Press, 2024)
Banglan Cai,1,2,* Manman Qi,2,3,* Xue Zhang,1,2 Denghai Zhang1- 3 1School of Basic Medicine, Ningxia Medical University, Yinchuan, People's Republic of China; 2Shanghai Health Commission Key Laboratory of Artificial Intelligence (AI)-Based Management of Inflammation and Chronic Diseases, Shanghai Pudong Gongli Hospital, Shanghai, People's Republic of China; 3School of Medicine, Shanghai University, Shanghai, People's Republic of China*These authors contributed equally to this workCorrespondence: Denghai Zhang; Xue Zhang, Shanghai Health Commission Key Laboratory of Artificial Intelligence (AI)-Based Management of Inflammation and Chronic Diseases, Shanghai Pudong Gongli Hospital, Shanghai, 200135, People's Republic of China, Tel +86-18916173857 ; +86-13524805404, Email Denghai_zhang@163.com; 2021021020@nxmu.edu.cnBackground: As a traditional Chinese medicine monomer derived from Tripterygium wilfordii Hook.f. with potential anticancer activity, celastrol can induce ferroptosis in hepatic stellate cells and inhibit their activation to alleviate liver fibrosis. Activation of ferroptosis can effectively inhibit Hepatocellular carcinoma (HCC). Whether celastrol inhibits HCC by inducing ferroptosis remains to be studied.Purpose: To explore the potential targets of celastrol against HCC through ferroptosis based on network pharmacology and to verify the anticancer effect of celastrol on HepG2 cells.Methods: We collected celastrol targets, HCC, and ferroptosis-related genes through online databases, and got their intersection targets. Subsequently, we obtained a protein-protein interaction (PPI) network, and performed gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis to gain key genes for further study. They were verified in vitro and were performed molecular docking. The changes in cell proliferation and ferroptosis characteristics of HepG2 cells after celastrol treatment were detected.Results: 31 core target genes were screened for PPI network and enrichment analysis. The most significantly related KEGG pathway was chemical carcinogenesis-reactive oxygen species. The mRNA and protein levels of GSTM1 were significantly decreased after celastrol treatment. Molecular docking demonstrated the interaction between celastrol and GSTM1. Ferroptosis was induced and cell proliferation was inhibited by celastrol in HCC cells.Conclusion: Celastrol induces ferroptosis in HCC via regulating GSTM1 expression and may serve as a novel therapeutic compound with clinical potential in HCC treatment. Keywords: network pharmacology, celastrol, hepatocellular carcinoma, ferroptosis, reactive oxygen species